2013
DOI: 10.1021/nl402813q
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Reversible Aggregation of Gold Nanoparticles in Polymer Nanocomposites through Hydrogen Bonding

Abstract: The ability to tune the state of dispersion or aggregation of nanoparticles within polymer-based nanocomposites, through variations in the chemical and physical interactions with the polymer matrix, is desirable for the design of materials with switchable properties. In this study, we introduce a simple and effective means of reversibly controlling the association state of nanoparticles based on the thermal sensitivity of hydrogen bonds between the nanoparticle ligands and the matrix. Strong hydrogen bonding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
70
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 46 publications
0
70
0
3
Order By: Relevance
“…[33][34][35][36][37] Using highlycontrolled synthesis and characterization techniques, a few experiments have also shown that particle dispersion and aggregation is tuned by enthalpic interactions between grafted and matrix chains. [37][38][39][40] Especially in the case where there are attractive enthalpic interactions between the graft and matrix chains, the mixture is driven to a dispersed phase even with grafts that are shorter than matrix chains, a case where chemically identical systems would exhibit dewetting and particle aggregation. 38 This ability to disperse particles due to graft-matrix miscibility allows for higher filler loadings than athermal chemically identical graft-matrix composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36][37] Using highlycontrolled synthesis and characterization techniques, a few experiments have also shown that particle dispersion and aggregation is tuned by enthalpic interactions between grafted and matrix chains. [37][38][39][40] Especially in the case where there are attractive enthalpic interactions between the graft and matrix chains, the mixture is driven to a dispersed phase even with grafts that are shorter than matrix chains, a case where chemically identical systems would exhibit dewetting and particle aggregation. 38 This ability to disperse particles due to graft-matrix miscibility allows for higher filler loadings than athermal chemically identical graft-matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…38 Choosing graft-matrix polymers with specific H-bonding also enables thermoreversibility to particle dispersion-aggregation. 40 In the above studies, the wetting-dewetting transition and dispersion-aggregation transition have been assumed to occur simultaneously, and are treated synonymously. 10,12,20,22,[24][25][26][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…However, in none of these systems were optical properties of the assemblies investigated. Another strategy for achieving DSA of NPs into dense arrays is using polymer nanocomposites [48][49][50] . Unfortunately, this strategy suffers from the complexity of achieving initial dispersion of NPs, low NP loadings 51 and usually collective interactions of NPs were not examined.…”
mentioning
confidence: 99%
“…Unfortunately, this strategy suffers from the complexity of achieving initial dispersion of NPs, low NP loadings 51 and usually collective interactions of NPs were not examined. Only lately, chiral plasmonic DNA nanostructures with switchable circular dichroism 52 , and switchable dispersion of Au NPs with reversible tunability of the aggregate optical characteristic were obtained 50 . Plasmonic band shifting by 5 nm was observed in the latter report after thermal annealing of the material for tens of minutes.…”
mentioning
confidence: 99%
“…17,18 Excellent NP dispersion was achieved presumably due to the existence of multiple hydrogen bonds between the NPs and the polymer matrix, a concept that has been used in previous works. For example, Heo et al 19 used gold NPs grafted with 2.8 kg.mol -1 (noted K in the future use) P(S-r-2VP) chains (grafting density of 1.7 chains/nm 2 ) in a 24.4 K P(S-r-4VPh) matrix. While the H-bonding between the OH group on the vinyl phenol moieties groups in the matrix and the nitrogen of the ligand grafted on the NPs ensures good miscibility, the consequences of this improved miscibility on mechanical properties has not been investigated.…”
mentioning
confidence: 99%